2010
DOI: 10.1080/15348421003738785
|View full text |Cite
|
Sign up to set email alerts
|

Demon Hunters and Hegemony: Portrayal of Religion on the CW'sSupernatural

Abstract: The authors analyze the religious themes and portrayals in the television program Supernatural, aired on the CW television network since 2005. As fictional entertainment programming, Supernatural incorporates various religions and lore into its episodes, which feature its protagonists fighting monsters, demons, and the occasional evil human. Findings from a content analysis of 60 episodes from the first 3 seasons illustrate a religious hegemony that forwards Catholicism, in the form of weapons used to fight ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Skill, Robinson, Lyons, and Larson (1994) found that about 6% of characters on network television had discernible religious affiliations in the mid-1990s, a level replicated by Clarke (2005) in 2002. Whenever portrayed, however, religion on U.S. television tends to be predominantly Christian, reflecting the majority and hegemonic position (Engstrom & Valenzano, 2010) and treated as gene rally positive (Lewis, 2002).…”
Section: Muslims Arabs and Us Mediamentioning
confidence: 98%
“…Skill, Robinson, Lyons, and Larson (1994) found that about 6% of characters on network television had discernible religious affiliations in the mid-1990s, a level replicated by Clarke (2005) in 2002. Whenever portrayed, however, religion on U.S. television tends to be predominantly Christian, reflecting the majority and hegemonic position (Engstrom & Valenzano, 2010) and treated as gene rally positive (Lewis, 2002).…”
Section: Muslims Arabs and Us Mediamentioning
confidence: 98%
“…Heroes and leaders in fictional programming are typically depicted as secular (Engstrom & Valenzano, 2010;Grigg, 2007). When theists are featured, they tend to be portrayed negatively, as old-fashioned, out of touch, and even dangerous (Lichter et al, 1994).…”
Section: Pervasiveness Of the Secular Narrative In Societal Discoursementioning
confidence: 99%
“…In addition, it centered on the role of the Church in broadening political dominance by arguing that "the Protestant Ascendancy has used the religious and sectarian divisions to shore up its political base and to advance a conservative form of politics that espoused as "natural" social order" (p. 62). In relation to McManus, Engstrom and Valenzano (2010) probed into the perceived interrelated function of religion and mass media. They conducted a content analysis of 60 episodes of the television program Supernatural aired from 2005-2008 and found that religious hegemony forwards Catholicism "in the form of weapons used to fight evil, such as holy water, and depictions of priests, as the main and most powerful opponent of evil" (p. 67).…”
Section: Hegemony Subalternity and Resistancementioning
confidence: 99%